2020
DOI: 10.1177/1369433220974781
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of CFRP-confined reactive powder concrete-filled steel tubes under axial compression

Abstract: Reactive powder concrete-filled steel tubes (RPCFSTs) have become an important research target in recent years. In engineering applications, RPCFSTs can provide superior vertical components for high-rise and tower buildings, thereby enabling developers to provide more floor space. However, this type of composite structure is prone to inelastic outward local buckling. The use of carbon fiber reinforced polymer (CFRP) wrapping to suppress such local buckling has shown great potential in limited test results. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The advanced properties of (RPC) are associated with “improvement mechanisms” which refer to the super‐high strength, extreme durability, and superior toughness 6–8 . In recent years, a large number of studies have been carried out on RPC, mainly focusing on the influence of composition, 9–11 curing conditions, 6,12 and mix ratio 13,14 on the mechanical properties of RPC materials or components 7,15–17 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advanced properties of (RPC) are associated with “improvement mechanisms” which refer to the super‐high strength, extreme durability, and superior toughness 6–8 . In recent years, a large number of studies have been carried out on RPC, mainly focusing on the influence of composition, 9–11 curing conditions, 6,12 and mix ratio 13,14 on the mechanical properties of RPC materials or components 7,15–17 …”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] In recent years, a large number of studies have been carried out on RPC, mainly focusing on the influence of composition, 9-11 curing conditions, 6,12 and mix ratio 13,14 on the mechanical properties of RPC materials or components. 7,[15][16][17] However, from the literature survey, there have been few studies on the effect of primary defects, such as cracks and holes, on the mechanical properties of RPC. In the process of production or use of RPC components, Discussion on this paper must be submitted within two months of the print publication.…”
mentioning
confidence: 99%
“…This improvement is ascribed to the high strength-to-weight ratio, high corrosion resistance, easier application in narrowed spaces, lessening labor costs, and easiness in site handling for FRP composites (Ali et al, 2020; Aslam et al, 2021; El Ouni and Raza, 2021; Ilki et al, 2008; Pour et al, 2019; Raza et al 2019, 2021a, 2021b, 2021c; Raza and Rafique, 2020; Rafique et al, 2021). The FRP composites are advanced materials for the strengthening and stiffening of the structural elements (Ali and Forth, 2021; El-Kashif et al, 2020; Huang et al, 2020; İşleyen et al, 2021; Tu et al, 2019; Wang et al, 2015; Wu et al, 2006; Zhang et al, 2020; Li and Jiao, 2021; Zhu et al, 2005; Zeng et al, 2021). In this context, several studies were performed to investigate the axial compression performance of CFRP-wrapped concrete in a circular section (Al-Nimry and Neqresh, 2019; Cui and Sheikh, 2010; Ferrotto et al, 2018; Jiang and Teng, 2007; Khan et al, 2020; Lam and Teng, 2003, 2004; Lam et al, 2006; Lin and Teng, 2019; Mirmiran et al, 1998; Spoelstra and Monti, 1999; Shahawy et al, 2000; Smith et al, 2010; Teng et al, 2009; Rousakis et al, 2012; Xiao and Wu, 2003; Youssf et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the existing tensile strength calculation formula, a tensile strength calculation equation suitable for tubular column filled with RPC is proposed. Liu et al, [13] Chen and Hou, [14] Zhu et al, [15] and Li et al [16] studied the bearing capacity and deformation performance of tubular columns filled with RPC under axial pressure, analyzed the influence of different parameters on the bearing capacity, and developed an applicable bearing capacity calculation formula. So far, no research has been found on the seismic performance of tubular columns filled with RPC under cyclic lateral loading.…”
mentioning
confidence: 99%